7z-1=8z-6

Simple and best practice solution for 7z-1=8z-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7z-1=8z-6 equation:


Simplifying
7z + -1 = 8z + -6

Reorder the terms:
-1 + 7z = 8z + -6

Reorder the terms:
-1 + 7z = -6 + 8z

Solving
-1 + 7z = -6 + 8z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-8z' to each side of the equation.
-1 + 7z + -8z = -6 + 8z + -8z

Combine like terms: 7z + -8z = -1z
-1 + -1z = -6 + 8z + -8z

Combine like terms: 8z + -8z = 0
-1 + -1z = -6 + 0
-1 + -1z = -6

Add '1' to each side of the equation.
-1 + 1 + -1z = -6 + 1

Combine like terms: -1 + 1 = 0
0 + -1z = -6 + 1
-1z = -6 + 1

Combine like terms: -6 + 1 = -5
-1z = -5

Divide each side by '-1'.
z = 5

Simplifying
z = 5

See similar equations:

| 2k+48=6k | | 6*.80= | | -6(x-2)=5x+32 | | 33-x+5=15 | | 16x+8=50+10x | | 12*u-5*u=14 | | 8n-(-2)/7 | | -5(2x-3)=-5 | | (-4x)=32 | | 2*x-x=18 | | 7.5/5=18/x | | f(x)=3(a)x | | -1/6÷1/2 | | =(2x)2-50 | | -4(5+2x)=84 | | -19x-34=65-x | | x-(-3)=-11 | | 10*c-9*c=7 | | f(x)=32(1.75)x | | r-8=-7 | | 4x+4(6x+5)=188 | | 3(3.33+1.66)+5y=10 | | 458.62=190+1.21x | | 8.6-12= | | 7x+8y=60 | | 4x^2+12+9= | | 4q-q=9 | | =3x-2 | | 3(3.67)+4=15 | | 8x+2=3x+9 | | y/5-5=1 | | 6+2(m-3)+10=3m |

Equations solver categories